The effects of victim testimony order and judicial education on juror decision-making in trials for rape - Lee, Harrison D. H. (Psychology, crime & law, 2024)
The victim’s testimony in most rape trials is unlikely to match jurors’ rape stereotypes and may instead seem typical of consensual sex. This research investigated whether providing judicial education about what commonly occurs in rape, and having a victim describe stereotype-consistent events early in their testimony, would guide jurors to interpret the victim’s testimony as depicting rape. After pilot work, community members (N = 212, 3 non-binary, 113 females, 96 males) received either educative instructions or standard instructions and watched video testimony in which the victim described the details of the assault at the beginning or end of the testimony. Participants also evaluated whether the testimony depicted rape or consensual sex as the events were described. Further, participants then read that another juror thought that the defendant was not guilty, and we re-assessed participants’ perceptions of the case. Participants who received the assault early categorised events as depicting rape. While educative instructions had no effect on evaluations of the testimony, participants who received education were more likely to find the defendant guilty. However, regardless of condition, participants perceived the defendant as less likely to be guilty after reading the juror’s statement compared to before. Recommendations for trial interventions are discussed.